Pengembangan Model Spot Capturing Problem untuk Membangun Karakter Siswa Sekolah Dasar - Freddy Widya Ariesta; Dewi Liesnoor Setyowati; Eko Purwanti (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2017)
This study aims to develop a spot capturing problem-based model that teachers can use to foster student character values in elementary schools. The type and the research design used are Research and Development (R&D) according to Borg & Gall with research methods using experimental quasi one group pretest posttest study. The research data was taken using instrument observation sheet and questionnaire then analyzed using quantitative descriptive percentage. This study produced a spot capturing problem-based model consisting of six learning steps: (1) students’ orientation, (2) organizing students, (3) conducting investigations and troubleshooting, (4) presents the investigation results, (5) evaluation and reflection, (6) follow-up. The validity of the problem-based spot capturing learning model was obtained from an expert validation assessment with a score of 85.7%. The results of the limited trials show that the problem-based spot capturing model is effective to cultivate the character of the students in the elementary school: caring character obtained a score of 78% (good) and responsible character obtained score of 82% (very good). Spot capturing model based on practical problems used in elementary school learning is seen from student and teacher response questionnaire obtained an average score of 82.5% (practical).